2015
DOI: 10.1128/jcm.03434-14
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Microorganisms from Sterile Body Fluids by Use of FilmArray

Abstract: Early detection and rapid identification of microorganisms are crucial the for appropriate management of infections of normally sterile body fluids (SBF) (1-3). Previously, SBF other than blood were cultured on solid medium (4). Larger volumes were processed through centrifugation and filtration in order to concentrate and improve the detection of microorganisms. Nonetheless, the microorganism recovery from SBF was unsatisfactory until the introduction of blood culture (BC) bottles. The introduction of BC bott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…Altun et al (90) evaluated the performance of the FilmArray BCID panel for the identification of organisms from positive blood culture bottles that had been inoculated with normally sterile body fluids (including pleural [n ϭ 51], synovial [n ϭ 38], abscess [n ϭ 10], dialysis [n ϭ 9], cerebrospinal [n ϭ 7], and bile [n ϭ 1] fluids). Those authors reported that the BCID panel accurately identified 100% (84/84) of organisms in monomicrobial infections and 75% (18/24) of targets if multiple organisms were recovered by routine culture (90). Of note, the FilmArray BCID panel is not FDA approved/cleared for direct testing of clinical specimens or of specimens other than blood in positive blood culture bottles.…”
Section: Multiplex Detection Of Pathogens From Sterile Body Fluidsmentioning
confidence: 99%
“…Altun et al (90) evaluated the performance of the FilmArray BCID panel for the identification of organisms from positive blood culture bottles that had been inoculated with normally sterile body fluids (including pleural [n ϭ 51], synovial [n ϭ 38], abscess [n ϭ 10], dialysis [n ϭ 9], cerebrospinal [n ϭ 7], and bile [n ϭ 1] fluids). Those authors reported that the BCID panel accurately identified 100% (84/84) of organisms in monomicrobial infections and 75% (18/24) of targets if multiple organisms were recovered by routine culture (90). Of note, the FilmArray BCID panel is not FDA approved/cleared for direct testing of clinical specimens or of specimens other than blood in positive blood culture bottles.…”
Section: Multiplex Detection Of Pathogens From Sterile Body Fluidsmentioning
confidence: 99%
“…These approaches comprise a potential point-of-care diagnostic tool with high sensitivity and specificity in direct identification of pneumococci especially from positive blood culture bottles. 52 However further studies analyzing the clinical significance of positive results in samples from patients with pneumococcal infections are warranted.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Many molecular assays have been developed to improve the turnaround time (TAT) of blood cultures using PCR and microarray technologies. Some of these assays are highly sensitive and reduce the TAT significantly and have been used by many clinical laboratories [10]. However, there are important limitations to these assays.…”
Section: Introductionmentioning
confidence: 99%